English Teacher’s Challenges and Solutions in Teaching Intellectual Disability Students: Case Study - Sab’na, Sab’na; Nasrullah, Nasrullah; Rosalina, Elsa (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2024)
English teaching is now inclusive in nature, which means it involves everyone without leaving any one behind. This is also the basis for English language education being everyone's right, including special needs. There is several research on teaching English specifically for disabilities that are very useful for helping teachers' teaching methods, improving strategies, and updating teaching materials. Yet, only a few studies talk about students with intellectual disability. Therefore, the aim of this research is to investigate the English language teaching in the form of challenges and the solutions, this research focused to analyse English teacher’s challenges and solutions in teaching students with mild intellectual disability in SLBN 1 Martapura. Qualitative method is used in this research. To collect the data needed, the observation and interview were done to an English teacher. The finding revealed that the challenges faced by English teacher were challenges in; a) classroom management, b) dealing with students' lack of general cognition, c) overcoming students' lack of focus, d) overcoming students' short memories, e) improving students' English vocabulary pronunciation. Furthermore, the solutions to solve those challenges were by a) using a group learning model, b) choosing fun media and method, c) using concrete objects, 4) using ice breaking, d) references modification, 5) repetition. Thus, English teacher faced many challenges in teaching students with mild intellectual disability. Indeed, there are several previous studies that discuss this issue, however, it is still too little. Thus, the researcher has an urgency to research more so that research for students with intellectual disability is more accommodated.